2021
DOI: 10.1016/j.isci.2021.102988
|View full text |Cite
|
Sign up to set email alerts
|

A worked bone assemblage from 120,000–90,000 year old deposits at Contrebandiers Cave, Atlantic Coast, Morocco

Abstract: Summary The emergence of Homo sapiens in Pleistocene Africa is associated with a profound reconfiguration of technology. Symbolic expression and personal ornamentation, new tool forms, and regional technological traditions are widely recognized as the earliest indicators of complex culture and cognition in humans. Here we describe a bone tool tradition from Contrebandiers Cave on the Atlantic coast of Morocco, dated between 120,000–90,000 years ago. The bone tools were produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…180 ka is consistent with climate change during the Pliocene–Pleistocene boundary where climate oscillations resulted in range contraction of species during dry arid climate periods (deMenocal, 1995 ; Hewitt, 2004 ). The observed bottleneck is also consistent with the emergence of Homo sapiens in East Africa some 200,000 years ago (McDougall et al, 2005 ; White et al, 2003 ) which was associated with updated and improved technology (Bradfield et al, 2020 ; Hallett et al, 2021 ). African hominins were known for hunting terrestrial prey and the development of advanced tools facilitated the incorporation of animal protein into their diets (Faith, 2014 ).…”
Section: Discussionsupporting
confidence: 69%
“…180 ka is consistent with climate change during the Pliocene–Pleistocene boundary where climate oscillations resulted in range contraction of species during dry arid climate periods (deMenocal, 1995 ; Hewitt, 2004 ). The observed bottleneck is also consistent with the emergence of Homo sapiens in East Africa some 200,000 years ago (McDougall et al, 2005 ; White et al, 2003 ) which was associated with updated and improved technology (Bradfield et al, 2020 ; Hallett et al, 2021 ). African hominins were known for hunting terrestrial prey and the development of advanced tools facilitated the incorporation of animal protein into their diets (Faith, 2014 ).…”
Section: Discussionsupporting
confidence: 69%
“…Three of the studied specimens were associated with the “Aterian” 14 , a typological variant of the Maghrebian MSA lithic industries that dominates the archaeological record west of the Nile Valley between 145 15 and 30 ka BP. As early as 142 ka BP, Aterian material culture documents the emergence of modern behavior 14 , 16 in the form of perforated and ochre-decorated Tricia (Nassarius) shells 17 , hearths and stone-walled structures 18 as well as formal bone tools 19 – 21 . The three hereafter referred to as Aterian individuals (Supplementary Table S1 ) were recovered in close vicinity to each other from cave sites in littoral Maghreb, namely Grotte des Contrebandiers, Dar-es-Soltane II and El Harhoura 1.…”
Section: Introductionmentioning
confidence: 99%
“…Low-power, stereo-microscopes are readily accessible, provide a good depth of field for larger areas and provide an appropriate scale at which to observe the distribution and extent of polishes and the boundaries between zones of contact (Rots 2005;Buc, Loponte 2007;Gates St-Pierre 2007;Evans, Donahue 2008;Buc 2011;Van Gijn 2014). Contrary to what some authors have suggested (e.g., Odell, Vereecken 1980;Choyke, Daróczi-Szabó 2010;Akhmetgaleeva 2017;Zhilin 2017;Halett et al 2021), most analysts, including myself, have found magnifications much below 100x insufficient to identify contact materials, except perhaps at a generic level of hard vs soft. Indeed, the low-power micrographs provided by some of the above-referenced authors do not show sufficient detail to be able to confidently identify the contact material responsible for polish formation (cf.…”
Section: Magnifications In Use-wear Studiesmentioning
confidence: 99%